Study of Aluminum-Free Complex Leavening Agent for Preparation of Deep-Fried Twisted Dough Stick - Guoquan, Ju; Yueying, Liu (Asian Journal of Chemistry, 2010)
Alum (AlK(SO4)2·12H2O) was used widely in the preparation of the traditional chinese wheat flour food, deep-fried twisted dough stick (DFTDS) as a leavening agent. However, alum was harmful to human health for long-term intake because of its high aluminum contents. The aim of the study is to determine effects of the aluminum-free complex leavening agent (AFCLA) in the preparation of deep-fried twisted dough stick. Through orthogonal tests and sensory evaluation, the optimal combination of aluminum-free complex leavening agent was identified, that 3.2 % sodium bicarbonate, 2.8 % glucono-delt-lactone, 0.4 % cream tartar and 0.8 % calcium dihydrogen phosphate. It could be used to replace alum completely as both leavening agent and nutrients and was great significance to improve the processing technology in the preparation of deep-fried twisted dough stick.